Definition of “Personal Information” in the Crime of Infringing on Citizens’ Personal Information—From the Perspective of Personal Information Protection Law - Yan Chang (Law and Economy, 2023)
The concept of “personal information” in the crime of infringing on citizens’ personal information has always been controversial in the criminal law circle. With the promulgation of the personal information protection law, it is necessary to further analyze the definition of “personal information” in the crime of infringing on citizens’ personal information. The legal interest of the crime of infringing on citizens’ personal information is not the suprapersonal legal interest, but the personal information right in the personal legal interest. As the core content of personal information right, the essence of information self-determination right is to emphasize citizens’ personal control over information, which is in line with the legislative orientation of the new law. Around the right of information self-determination, personal information without identifiability should not belong to personal information, and the identification object of personal information should also be limited to “natural persons” to prevent the biased application of law in judicial practice.